'Andare verso il popolo (Moving Towards the People)': Classicism and Rural Architecture at the 1936 VI Italian Triennale. Issue 1 (2nd September 2021) - Ricchi, Daria
Abstract : At the sixth Milan Triennale in 1936, entitled 'Continuity-Modernity', Giuseppe Pagano and Edoardo Persico displayed two divergent but complementary ideological and aesthetic positions: leaning toward classicism and showcasing rural examples, respectively. This article focuses on how these two approaches share similarities with the idea of populism, a concept often associated with dictatorial regimes. Populism implies a defined and strict notion of people and of national identity. This article explores the relevance of the expression 'andare verso il popolo', here translated as 'moving towards the people', a term used by Pagano in an article in Casabella of 1935 to define what a national architecture could be. It also explores how architecture can be popular without being populist. The central argument is that the phrase 'moving towards the people' became a politicised expression embodying two contrasting conceptions of a populism in which architectural ideas playing a defining role. The context is the architectural discourse during the controversial period of the Fascist regime and the rationalist debate in Italy between 1928 and 1936. The two main venues of the architectural debate were Casabella, which the same Pagano and Persico had been editing since 1931, and Quadrante, founded by the intellectual and literary figures Pietro Maria Bardi and Massimo Bontempelli in 1933. The two different aesthetic positions of Persico and Pagano within the 1936 Triennale would later be associated with two contrasting lines of populism: one more conservative and associated with the Fascist regime, and the other more reactionary that influenced the resistenza of the left.